Implementation of the provisions of Articles 2 and 10 paragraph (1) of Regent's Regulation Number 28 of 2013 on Rusunawa Management in Klaten Regency: Implementasi Ketentuan Pasal 2 dan 10 ayat (1) Peraturan Bupati Nomor 28 Tahun 2013 pada Pengelolaan Rusunawa Kabupaten Klaten - Apriyanti, Zahra Arintiya (Annual Review of Legal Studies, 2024)
The construction of flats through Klaten Regent Regulation Number 28 of 2013 concerning Management of Simple Rental Flats in Klaten Regency is one of the solutions from the Klaten Regency regional government in meeting the need for adequate housing with a maximum rental system of 6 (six) years. This research aims to find out how Article 10 paragraph (1) of Regent Regulation Number 28 of 2013 is implemented. The type of research used is empirical juridical research with a qualitative research approach. Data collection techniques in this research were carried out through interviews, observation and literature study. The data validity technique used in this research uses data triangulation validity techniques. The results of this research can be concluded that the implementation of Article 10 paragraph (1) of Regent Regulation Number 28 of the Year has not been effective, where there are 50% of residents who have occupied more than the maximum rental period of 6 (six) years, which is also exacerbated by 59% of residents who have not been able to afford it. prepare a permanent residence. This problem arises because the Regional Government of Klaten Regency has not been firm in implementing existing policies. The action to resolve this problem is to provide a financial assistance program for the construction of housing for flat residents who already have assets in the form of land and continue to allow flat residents who have lived in the flat for more than 6 (six) years to continue living in the flat until the residents can prepare and/or have a permanent residence. The regional government of Klaten Regency, through the flats, is able to realize prosperity and benefits, but there is still a need for harmonization between implementation and existing regulations.